2007
DOI: 10.4315/0362-028x-70.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Transportation of Feedlot Cattle to the Harvest Facility on the Prevalence of Escherichia coli O157:H7, Salmonella, and Total Aerobic Microorganisms on Hides

Abstract: Prevalences of Escherichia coli O157:H7, Salmonella, and total aerobic microorganisms were determined on the hides of beef feedlot cattle before and after transport from the feedyard to the harvest facility in clean and dirty trailers. Swab samples were taken from the midline and withers of 40 animals on each of 8 days before and after shipping. After samples were collected, animals were loaded in groups of 10 on upper and lower levels of clean and dirty trailers. Animals were unloaded at the harvest facility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 8 publications
0
10
1
Order By: Relevance
“…Trailer cleanliness has not consistently influenced contamination of cattle with E. coli O157, and trailer cleaning might be less critical when the incidence of the organism is low (12,23). Accordingly, in the present study, prevalence of E. coli O157 did not increase (P .…”
Section: Resultscontrasting
confidence: 45%
“…Trailer cleanliness has not consistently influenced contamination of cattle with E. coli O157, and trailer cleaning might be less critical when the incidence of the organism is low (12,23). Accordingly, in the present study, prevalence of E. coli O157 did not increase (P .…”
Section: Resultscontrasting
confidence: 45%
“…Previous analysis of the aerobic bacterial load (aerobic plate count [APC]) of hide and preevisceration carcass samples collected in this study (n Ï­ 3,040 for each sample site) showed that on average Ïł1.7% (95% CI, 0.96 to 3.13%) of hide contamination was observed to be transferred to carcasses during the dressing process (15). Also, numerous studies have shown that cattle hide hygiene is significantly affected by transportation and lairage prior to slaughter (5,24,49,63). Accordingly, measurements of hide pathogen prevalence at harvest are an essential aspect of both understanding the magnitude of risk and determining what control measures may be necessary to mitigate those risks.…”
Section: Discussionmentioning
confidence: 89%
“…It was not determined in either of these studies if these isolates were found on the hides of cattle after transport, or if they were ever transferred to the carcasses. Reicks et al reported that Salmonella prevalence on the hides of animals increased after transport, but could not attribute the change to the cleanliness of the trailers (21). In previous work, Arthur et al found 7 of 8 tractor trailers to harbor E. coli O157:H7 prior to loading cattle (1).…”
Section: Discussionmentioning
confidence: 99%